LEGAL POSITION OF ANIMALS IN CIVIL LAW: FROM OBJECTS TO SUBJECTS OF LAW (Heritage, 2022)
The legal position of animals in civil law, as well as in other branches of law, seeks its foundations in moral / ethical principles. Various philosophical debates have often been a stumbling block to the recognition of the moral rights of animals. The historical challenge has led to courts around the world, casually, challenging moral rights, making decisions in not the best interest of animals. We have witnessed, throughout history, different points of view and approaches to their legal position. Starting from the status of an object of property, which did not exercise legal protection because of its value, but because of the interests of people, all the way to the current view that animals are at the same time subjects and objects of rights. Today, their sui generis legal subjectivity gives them legal capacity for some non-property rights. Also, their specificity is reflected in the fact that at the same time they have the legal position of the objects of law, and property. Although these are living beings who have a developed nervous system, feelings of pain, suffering, stress, fear and the like, the law "worked" exclusively in one direction: distinguishing humans from animals.
Keywords: animal rights, legal status of animals, subjects of law, objects of law, civil law